A study on children customary clothes in Malay head shaving: cukur jambul ceremony for the Malay royal tradition / Nor Idayu Ibrahim ... [et al.] - Ibrahim, Nor Idayu; Zakaria, Muhammad Salehuddin; Zainuddin, Nasaie; Zakaria, Muhammad Hisyam (Universiti Teknologi MARA, Perak, 2022)
This Study aims to discover and document the clothing customarily worn by children during the Malay head shaving ceremony (Cukur Jambul), a tradition observed by the Malay Royal family. The head shaving ceremony is a unique Malay tradition and custom, relating to the birth of a new baby into the royal family and the Tradisi Agung custom. This study emphasizes Mayer Schapiro's theory of style in the context of artefacts or material cultural objects. It applies a qualitative method due to its flexibility in recording the views of informants in relation to observations. Specifically, this research considers a collection of photographs taken during head shaving ceremonies. The observation on Malay royal family tradition continues to uphold the uses of Songket ("The queen of textiles") in most of their ceremonies until today. Overall, this study will provide an invaluable source of information about Malay custom and culture. It will be of benefit to the Malay royal family, researchers, academics, scholars, students, cultural archivists, and museum curators interested in studying and preserving this subject and tradition.